Municipal solid waste treatment for bioenergy and resource production: Potential technologies, techno-economic-environmental aspects and implications of membrane-based recovery. (May 2023) - Amin, Naila; Aslam, Muhammad; khan, Zakir; Yasin, Muhammad; Hossain, Shakhawat; Shahid, Muhammad Kashif; Inayat, Abrar; Samir, Ahmed; Ahmad, Rizwan; Murshed, Mohammad N.; Khurram, Muhammad Shahzad; El Sayed, Mohamed E.; et al.
Abstract: World estimated municipal solid waste generating at an alarming rate and its disposal is a severe concern of today's world. It is equivalent to 0.79 kg/d per person footprint and causing climate change; health hazards and other environmental issues which need attention on an urgent basis. Waste to energy (WTE) considers as an alternative renewable energy potential to recover energy from waste and reduce the global waste problems. WTE reduced the burden on fossil fuels for energy generation, waste volumes, environmental, and greenhouse gases emissions. This critical review aims to evaluate the source of solid waste generation and the possible routes of waste management such as biological landfill and thermal treatment (Incineration, pyrolysis, and gasification). Moreover, a comparative evaluation of different technologies was reviewed in terms of economic and environmental aspects along with their limitations and advantages. Critical literature revealed that gasification seemed to be the efficient route and environmentally sustainable. In addition, a framework for the gasification process, gasifier types, and selection of gasifiers for MSW was presented. The country-wise solutions recommendation was proposed for solid waste management with the least impact on the environment. Furthermore, key issues and potential perspectives that require urgent attention to facilitate global penetration are highlighted. Finally, practical implications of membrane and comparison membrane-based separation technology with other conventional technologies to recover bioenergy and resources were discussed. It is expected that this study will lead towards practical solution for future advancement in terms of economic and environmental concerns, and also provide economic feasibility and practical implications for global penetration. Graphical abstract: Image 1 Highlights: Current practices and technologies for MSW are critically reviewed. Energy production and resources recovery potential with different platforms are analyzed. Techno-economic and environmental prospects are critically discussed. Potential of membrane technology for bioenergy and resource recovery. Future perspectives and key issued required urgent attention are highlighted.